Relationships Between Wood-Anatomical Features and Resistance Drilling Density in Norway Spruce and European Beech - Arnič, Domen; Krajnc, Luka; Gričar, Jožica; Prislan, Peter (Frontiers in Plant Science, 2022)
Environmental conditions affect tree-ring width (TRW), wood structure and, consequently, wood density, which is one of the main wood quality indicators. Although studies on inter- and intra-annual variability in tree ring features or density exist, studies demonstrating a clear link between wood structure on a cellular level and its effect on wood density on a macroscopic level are rare. Norway spruce with its simple coniferous structure and European beech, a diffuse porous angiosperm species was selected to analyse these relationships. Increment cores were collected from both species at four sites in Slovenia. In total, 24 European beech and 17 Norway spruce trees were sampled. In addition, resistance drilling measurements were performed just a few centimetres above the increment core sampling. TRW and quantitative wood anatomy measurements were performed on the collected cores. Resistance drilling density values, tree-ring (TRW, earlywood width–EWW, transition-TWW and latewood width–LWW) and wood-anatomical features (vessel/tracheid area and diameter, cell density, relative conductive area, and cell wall thickness) were then averaged for the first 7 cm of measurements. We observed significant relationships between tree-ring and wood-anatomical features in both spruce and beech. In spruce, the highest correlation values were found between TRW and LWW. In beech, the highest correlations were observed between TRW and cell density. There were no significant relationships between wood-anatomical features and resistance drilling density in beech. However, in spruce, a significant negative correlation was found between resistance drilling density and tangential tracheid diameter, and a positive correlation between resistance drilling density and both TWW+LWW and LWW. Our findings suggest that resistance drilling measurements can be used to evaluate differences in density within and between species, but they should be improved in resolution to be able to detect changes in wood anatomy.